The Relationship Between Strategic Planning and Budgeting in Regional Development Planning Agency of Sukabumi City - Adicipta, Fahmi; Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.04.TAHUN 2019, 2019)
This paper aims to analyze whether Coordination and synchronization of programs or activities and budgeting in regional development planning agency is possible. Lack of synchronization and coordination between SKPD externally so as to affect the quality of development planning. The Relationship Between Strategic Planning and Budgeting Is expected to play a role other than as a control tool, but it can also be used as a performance quality appraisal tool, as well as a tool for the realization of a clean and authoritative government (good governance). There are relationship between strategic planning in Regional Development Planning Agency of sukabumi city  (Renstra) and its budgeting. The relationship particularly can be seen in the flow of Renstra (from vision to activities) and the achievement from targets.